A comparison of vertical jump height measurements on the vertec and biotran using three jumping techniques - McCollum, J. D. (1995)
Abstract: The purpose of this study was to determine if differences exist between the Vertec and the BIOTRAN in measuring vertical jump height. Twenty five men and twenty five women from the University of North Carolina at Chapel Hill volunteered to perform five sets of three types of jumping techniques. Each jump was measured by two devices simultaneously, the Vertec and the BIOTRAN, for comparison. The Vertec was used as the standard measure. A Pearson Product Moment Correlation Coefficient indicated that a very strong correlation ( r=.9709, r=.7831) was found to exist between the original and the test-retest data for the standing jump, for both the Vertec and the BIOTRAN indicating that a very high percentage of the data was predictable. Independent T-tests for the standing, one-step, and two-step jumping techniques showed that no statistically significant differences were found to exist between the BIOTRAN and the Vertec measurements. Although a statistically significant difference may not exist, a consistent 3-4 inch deficit in the BIOTRAN data indicates that there are practical differences that do exist. It is suggested that these differences may be due to an inconsistency between the operational definitions of vertical jump height for each device. It is suggested that raising up from the flat footed position to the tip-toe position may account for the differences between the measurements made by the BIOTRAN and the Vertec. It is further recommended that this study be repeated, adopting the tip-toe position to determine the standing reach needed to calculate jump height on the Vertec. (McCollum, J.D. A comparison of vertical jump height measurements on the vertec and biotran using three jumping techniques, 1995. M.A., University of North Carolina at Chapel Hill. (40pp 1f $5.00) PE 3611)